PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KREATIVITAS KARYAWAN DENGAN SELF-EFFICACY CREATIVITY SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN NON BANK (STUDI KASUS PT PEGADAIAN CP KEROBOKAN - BADUNG) - A A Ayu teni pratiwi; Putri Anggreni; Ni Putu Yuli Tresna Dewi (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to determine the effect of transformational leadership on employee creativity and employee Self-efficacy Creativity, as well as to determine the effect of self-efficacy creativity on employee creativity and to determine the effect of transformational leadership on employee creativity after being mediated with employee self-efficacy creativity at the Pegadaian Kc office. Kerobokan. This research is structured descriptively using a quantitative approach method. Primary data in this research was obtained through several questions given in questionnaires and interviews with respondents. Data obtained from secondary sources is obtained through company records or documentation, government publications, industry analysis provided by the media, web, internet, and others. Where is the object of this study Pawnshop employees Kc. Kerobokan. So that in the process of collecting data, interviews or direct observation of informants must be carried out, and researchers cannot provide temporary assumptions about this research. The results of this study are that first, transformational leadership has a significant effect on employee creativity. Second, transformational leadership has a significant effect on the creative self-efficacy of employees. Creative self-efficacy has a significant effect on creativity in employees. And Creative self-efficacy mediates the influence of transformational leadership on creativity in employees.